New and little‐known species of gall midges (Diptera, Cecidomyiidae) and other gall‐formers in the fauna of Dagestan - Z. A. Fedotova; G. M. Nakhibasheva; G. M. Mukhtarova; A. A. Teymurov; A. G. Gasangadzhieva (Юг России: экология, развитие)
Aim. To develop additional information about the diversity of gall‐forming insects in Dagestan, their distribution, trophic links and features of the formation of complexes of dominant species on common host plants.The materials were collected in the plains and mountains of Dagestan. Standard methods were used: plant inspection, search and mass collection of galls, wintering in laboratory conditions, breeding of imago and preparation of larval and imago slides.New and little‐known gall midges in the fauna of Dagestan (27 species from 16 genera) were identified: 1 species of lace bat (Hemiptera, Tingidae) and case‐bearer (Lepidoptera, Coleophoridae) and 2 species from 2 genera of gall wasps (Hymenoptera, Cynipidae) and mites (Acariformes, Eriophyidae) were identified. New Cecidomyiidae in the fauna of Dagestan were 25 species of 13 genera, of them 5 species of 5 genera were new in Russia: Asphondylia ziziphorae Fedotova, 1985, Contarinia perplicata Fedotova, 1997, Mycodiplosis glycyrrhizae Fedotova, 1985, Izeniola potanini (Fedotova, 1982) и Jaapiella inulicola Fedotova, 1993; 4 species were new for the Caucasus: Placochela nigripes (Löw, 1877), Arthrocnodax galiobiae Fedotova, 1997, Jaapiella volgensis Fedotova, 2008 and Macrolabis luceti Kieffer, 1899. Other gall‐formers include the mite Aceria galiobia (Canestrini, 1891), the case‐bearer Auagasma atraphaxidellum Kuznetsov, 1957, the gall wasps Aulacidea hieracii (Bouché, 1834) and Diastrophus rubi (Bouché, 1834), all new for Dagestan. Gall‐formers (33 species from 22 genera) were identified on plants of 28 species from 25 genera and 13 families, of which 5 species from 5 genera, including endemics of the Caucasus, are new host plants for gall midges and other gall‐forming plants.Information about the complexes of gall‐formers of Dagestan and their common plants is relevant for solving the problems of taxonomy, associated phylogeny and study of the evolutionary features of gall formation. Due to the poor study of the fauna of gall‐formers, trophic links and distribution, their economic significance and prospects for use for phytosanitary control in the creation of protected areas, parks and the use of agricultural fields have not been sufficiently assessed.